Clinical study of use of large C suture in procedure for prolapse and hemorrhoids for treatment of mixed hemorrhoids - Yu, Jia-He (J Int Med Res, 2021)
OBJECTIVE: To investigate the clinical use of a large C suture in the procedure for prolapse and hemorrhoids (PPH) for treatment of mixed hemorrhoids. METHODS: Patients with mixed hemorrhoids (grade III or IV) who underwent treatment with a large C suture during PPH in the Affiliated Hospital (Group) of Putian University from 1 April 2018 to 31 March 2019 were enrolled in this retrospective study. The incidences of anastomotic stenosis and anastomotic hemorrhage after the operation were observed. RESULTS: The study population comprised 126 patients (46 men and 80 women) ranging in age from 30 to 78 years (mean, 46.1 ± 2.5 years). Of these patients, 60 had circular mixed hemorrhoids, 36 had grade III circular internal hemorrhoids, and 30 had grade IV circular internal hemorrhoids. The onset time among all patients ranged from 0.5 to 25 years. All patients underwent 6 months of postoperative follow-up. None of the patients with mixed hemorrhoids developed anastomotic stenosis, although two patients developed secondary anastomotic bleeding. CONCLUSION: Placement of a large C suture during PPH is a reliable technique for treatment of mixed hemorrhoids. It is simple, effective, and applicable and can be helpful for a large number of patients in primary hospitals.